Laser-Induced Smoke in Dermatologic Practice: A Survey to Explore Hazard Perceptions, Safety Measures and Unmet Needs : Laser-Induced Smoke Study - Fransen , Frederike; Hiel, Marjolein; Al-Niaimi, Firas; Badawi, Ashraf; Haedersdal, Merete; Laubach, Hans-Joachim; Snauwaert, Johan; Wolkerstorfer , Albert (Journal of Lasers in Medical Sciences, 2022)
Introduction: Inhalation of laser-induced smoke is a potential health hazard to exposed physicians and laser operators. To date, little is known about the perception of health hazards related to laser-induced smoke exposure among physicians and the actual use of safety measures to mitigate these risks. Methods: In May 2020, 514 members of the European Society for Lasers and Energy-Based Devices (ESLD) were invited by email to participate in an online survey. The survey comprised 16 questions including multiple-choice and open-ended questions. Results: Responses were received from 109 participants. The majority (90%) were aware of potential hazards and highlighted a desire for better protective measures (60%). A smoke evacuation system was frequently used with ablative lasers (66%) and fractional ablative lasers (61%), but less the case with non-ablative lasers (30%) and hair removal lasers (28%). The COVID-19 outbreak had no clear effect on the use of smoke evacuation systems. Prior to the COVID-19 outbreak, mainly surgical masks were used (40-57%), while high filtration masks (FFP1, FFP2 or FFP3) were used by only a small percentage (15-30%). The post-COVID-19 outbreak, the use of high filtration masks increased significantly (54-66%), predominately due to an increase in the use of FFP2 masks. Reasons mentioned for inadequate protective measures were sparse knowledge, limited availability, discomfort, excessive noise, high room temperatures, and financial costs. Conclusion: While there is considerable awareness of the hazards of laser-induced smoke among physicians and laser operators, a substantial number of them do not use appropriate protective measures. The implementation of regulations on safety measures is hampered by sparse knowledge, limited availability, discomfort, excessive noise, financial issues, and high room temperatures